Worldwide spatial distribution of Tuta absoluta (Lepidoptera: Gelechiidae) and its natural enemies under current and future climatic change conditions through modelling - Santana Júnior, Paulo Antônio (2019)
In only 10 years the insect Tuta absoluta has become one of the most important threat for agriculture worldwide. Since its introduction in Spain in 2006, this pest has infected 60% of the tomato crops in many regions of the world. In this study, ecological niche models were built investigate the areas under risk of invasion of T. absoluta and the effect of climate change on it and four of its natural enemies (Neochrysocharis formosa, Stenomesius japonicus, Pseudapanteles dignus, and Macrolophus pygmaeus). We modelled the areas under risk and the effect of climate change on the pest and its natural enemies using CLIMEX and MaxEnt. Important tomato producers such as China, Mexico, the Netherlands, and the USA should be concerned about the risk of an eventual invasion of T. absoluta due to their climatic suitability for this pest. The increasing suitability for T. absoluta in open field in these countries will not be accompanied by an increase for some of the natural enemies. Therefore, this variation in suitability will have important consequences on biological control in these areas. Thus, this study allows pest management agencies to improve their biological control programs and quarantine measures against the tomato pinworm.